1999
DOI: 10.1046/j.1469-8137.1999.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection time and density influence the response of sorghum to the parasitic angiosperm Striga hermonthica

Abstract: Two cultivars of sorghum (CSH-1 and Ochuti) were grown in the presence and absence of the root hemiparasite Striga hermonthica in uniform conditions in the field in Kenya, Africa. S. hermonthica had a marked influence on growth and photosynthesis of ' CSH-1 ' ; however, ' Ochuti ' showed a less severe response to infection and tolerance of the parasite. The variation in genotype response might be partly explained by later attachment of the parasite and a lower level of infection. Laboratory studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
93
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 15 publications
13
93
0
2
Order By: Relevance
“…1A). The later establishment of infection in Azucena likely explains the higher tolerance to Striga, similar to what was observed in sorghum, where tolerant varieties generally exhibit later Striga emergence (40). Intriguingly, Striga postattachment resistance mapped to the same position on chromosome 1 as the QTL discussed in the present work (near marker C1370) in a cross between Nipponbare and Kasalath (21), with the Nipponbare allele conferring greater resistance (41).…”
Section: Discussionsupporting
confidence: 82%
“…1A). The later establishment of infection in Azucena likely explains the higher tolerance to Striga, similar to what was observed in sorghum, where tolerant varieties generally exhibit later Striga emergence (40). Intriguingly, Striga postattachment resistance mapped to the same position on chromosome 1 as the QTL discussed in the present work (near marker C1370) in a cross between Nipponbare and Kasalath (21), with the Nipponbare allele conferring greater resistance (41).…”
Section: Discussionsupporting
confidence: 82%
“…Koskela et al (2002) reported a similar relationship between parasite infection level and host damage for the holoparasite Cuscuta europaea parasitizing on Urtica dioica. Gurney et al (1999) found a negative and exponential relationship between yield and parasite load for Striga hermonthica parasitizing on sorghum, where parasite load was expressed as Striga dry weight. These findings do not necessarily contradict findings of the current study.…”
Section: Discussionmentioning
confidence: 97%
“…Determination of the relative yield loss already requires the presence of Striga-free control plots adjacent to Striga infested plots (e.g. Gurney et al, 1999;Rodenburg et al, 2005). Control plots in the field can be created by use of methyl bromide (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations